2022
DOI: 10.1186/s12893-022-01760-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for weight loss after Roux-en-Y gastric bypass: the trend and associated factors for weight loss

Abstract: Background Historically, Roux-en-Y gastric bypass (RYGB) has been considered the gold standard of bariatric surgery (BS). This procedure acts as a mixed restrictive and malabsorptive operation. Methods  This retrospective cohort study included 410 morbidly obese patients (BMI > 40 kg/m2 or BMI > 35 kg/m2 along with at least one major comorbidity) who underwent primary laparoscopic RYGB surgery from 2009 to 2015 by a single surgery team. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…On the downside, even though various factors have been identified as affecting the effectiveness of weight loss, the majority of the literature has limited these factors to patients’ anthropometric indicators or inspection indicators 18 , 41 , 42 . In addition, most recent studies only employed multivariate regression analysis to make predictions 43 45 , which were not sufficiently visual to be clinically applicable.…”
Section: Discussionmentioning
confidence: 99%
“…On the downside, even though various factors have been identified as affecting the effectiveness of weight loss, the majority of the literature has limited these factors to patients’ anthropometric indicators or inspection indicators 18 , 41 , 42 . In addition, most recent studies only employed multivariate regression analysis to make predictions 43 45 , which were not sufficiently visual to be clinically applicable.…”
Section: Discussionmentioning
confidence: 99%
“…This gastrojejunal anastomosis bypasses the proximal small intestine, a major nutrient digestion and absorption site, further contributing to weight loss in addition to mechanical restriction through the reduction in the overall size of the proximal stomach [32]. The RYGB procedure typically results in a loss of about 70% of excess body weight, or approximately 30% to 35% of total body weight [33]. Due to the bimodal restrictive and malabsorptive effects, RYGB has been shown to promote increased weight loss of up to 20% more than SG at 24 months, although it is considered a more difficult procedure [34].…”
Section: Roux-en-y Gastric Bypass (Rygb) and Gut Microbiotamentioning
confidence: 99%
“…Many studies have shown that type 2 diabetes is a prognostic factor for poor weight loss after MBS. 19,[26][27][28] Campos et al 26 found that diabetes was independently associated with poor weight…”
Section: Presence Of Diabetesmentioning
confidence: 99%
“…Many studies have shown that type 2 diabetes is a prognostic factor for poor weight loss after MBS. 19 , 26 - 28 Campos et al 26 found that diabetes was independently associated with poor weight loss (%EWL <40%) 1 year after RYGB, particularly in those using insulin before surgery. Still et al 19 confirmed that diabetes was independently associated with weight loss outcomes for up to 36 months after RYGB.…”
Section: Predictors Of Weight Loss After Mbsmentioning
confidence: 99%
See 1 more Smart Citation